Long-term trend in surface ozone in Houston-Galveston-Brazoria: Sectoral contributions based on changes in volatile organic compounds. (1st September 2022) - Soleimanian, Ehsan; Wang, Yuxuan; Estes, Mark
Abstract: This study investigated the long-term variations in ambient levels of surface ozone, volatile organic compounds (VOCs), and nitrogen oxides (NOx ) within the Houston-Galveston-Brazoria (HGB) region. Analysis of ozone levels revealed an overall reduction in the maximum daily 8-h average ozone (MDA8 O3 ) from 2000 to 2019 (April–October) with an average rate of ∼ −0.48 ppb/yr across HGB. With a few exceptions, the MDA8 O3 reduction rates were more pronounced for the monitoring sites closer to the Houston Ship Channel (HSC). Meanwhile, ambient levels of NOx and most VOC species (across the three representative sites as Houston Bayland Park, Haden Road, and Lynchburg Ferry) decreased significantly within the same investigation period, reflecting the impact of emission reductions. The positive matrix factorization (PMF) model applied to the mentioned sites identified regional background ozone, petrochemical emissions, engine combustion, natural gas/fuel evaporation, and solvent/painting/rubber industries as the major sources of MDA8 O3 . The regional background ozone was the predominant source, accounting for 59–70% of MDA8 O3 across the three sites. Regarding the local anthropogenic emissions, natural gas/fuel evaporation was the largest contributor (19.5 ± 6.1%) to MDA8 O3 at Houston Bayland Park, whereas petrochemical facilities (10.9 ± 4.9%) and solvent/painting/rubber industries (18.1 ± 9.5%) were the largest factor at Haden Road and Lynchburg Ferry, respectively. Notable reductions were found in the contributions of petrochemical emissions, engine combustion, and natural gas/fuel evaporation to MDA8 O3 within 2000–2019, but an increasing trend was revealed in the role of solvent/painting/rubber industries on MDA8 O3 most probably due to the enhanced demand for their products. Results of this study corroborated the success of emission control policies in limiting ozone precursors and provided useful details for prioritizing emission reduction policies to further reduce ozone pollution in the HGB. Graphical abstract: Image 1 Highlights: The ambient levels of O3 and most VOCs have decreased during 2000–2019 across HGB. Petrochemical/industrial sectors were major contributors to O3 formation near HSC. Natural gas/fuel evaporation were the major local sources of O3 in downwind areas. Emissions from solvent/painting/rubber industries have surged within last decade. Results underscored the effectiveness of emission mitigations targeting HRVOCs.